NAVIGATING DIGITAL DA’WAH: HANAN ATTAKI’S APPROACH AND NAHDATUL ULAMA’S AUTHORITY ON SOCIAL MEDIA - A'thoina, Inna; Abdullah Mustafa Mohamad Al-Aboosi (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
Hanan Attaki, founder of the Shift (a youth hijrah movement), pledged allegiance (bai’at) to Nahdlatul Ulama (NU), one of Indonesia’s most prominent traditionalist Islamic organizations, sparking significant responses from his extensive social media following of ten million on Instagram and two million on YouTube, most of whom are young people. This paper aims to explore the new step of Hanan Attaki’s da’wah and the religious authority of NU’s Ulema through social media by examining shifts in Hanan Attaki’s da’wah approach pre- and post-affiliation and investigating how his affiliation enhances the influence of NU’s ulema mainly through his social media platforms, using Fajri Alatas’ theory of religious authority. This study uses a qualitative method by analyzing content on the YouTube and Instagram accounts of Hanan Attaki using netlytic assistant. This paper argues that joining Hanan Attaki at NU is one of his da’wah strategies to spread da’wah across society, including the grassroots. At the same time, Hanan Attaki contributes to spreading the authority of NU ulema and its ideology among millennials through social media.